The relationship between body composition and blood pressure among primary school children in Eastern Cape province, South Africa - Howard Gomwe; Eunice Seekoe; Philemon Lyoka; Chioneso S. Marange (AOSIS, 2019)
Background: In South Africa, especially in the Eastern Cape province, despite reported high prevalence of underweight and obesity, little is known regarding the relationship of body composition (BC) with blood pressure (BP) in primary school children. Understanding the relationship between BC and BP in these children is important because it is associated with adverse effects on health and social repercussion in both adolescence and adulthood. Aim: The aim of this study was to examine the relationship between BC and BP among South African primary school children. Setting: This study was conducted on a cohort of primary school learners in the Eastern Cape Province of South Africa. Methods: A school-based cross-sectional survey was conducted among 876 school children aged 9-14 years, using multistage sampling techniques. Body mass and stature were measured using a calibrated scale. Anthropometric measurements including weight, height, waist circumference, triceps, gluteal and subscapular were also collected. Body mass index, percentage body fat and waist-to-hip ratio were calculated. Results: Of the 876 participants, 356 (40.6%) were boys and 520 (59.0%) were girls. The Spearman's rho correlation coefficients revealed positive significant correlations between systolic BP with age (r = 0.171; p 0.0001), stature (r = 0.205; p 0.0001), weight (r = 0.277; p 0.0001), body mass index (r = 0.243; p 0.0001), waist circumference (r = 0.259; p 0.0001), gluteal (r = 0.214; p 0.0001), triceps (r = 0.203; p 0.0001), subscapular (r = 0.167; p 0.0001), body fat percentage (r = 0.206; p 0.0001), fat mass (r = 0.257; p 0.0001) and fat-free mass (r = 0.238; p 0.0001). There was no statistically significant correlation between waist-to-hip ratio and systolic BP (r = 0.064; p = 0.059). In terms of diastolic BP, there existed no significant correlations with age (r = 0.026; p = 0.443) and waist-to-hip ratio (r = 0.002; p = 0.947). Collectively, the prevalence of hypertension was 76.4% in the normal group compared with those who were pre-hypertensive (18.4%) and hypertensive (5.3%). Girls showed a higher prevalence of pre-hypertension than boys (19.6% compared with 16.6%, respectively). Conclusion: There is a relationship between most of the BC variables and BP in children. The screening of BP as part of physical examinations of school children is necessary for early prevention and intervention programmes for hypertension.